Operative Atlas of Laparoscopic Reconstructive Urology - Ramalingam, Manickam; Patel, Vipul R. (Springer London : Imprint: Springer, 2009)
The Operative Atlas of Laparoscopic Reconstructive Urology is essential reading for all practicing urologists around the globe, offering a comprehensive visual walkthrough of common procedures. Written by leading international experts, and edited by two pioneers in the field of laparoscopic urology who have more than 2,000 surgeries between them, this title also describes common pitfalls to add further worth as a practical surgical manual. Many contributing authors are also highly active in robotic surgery, and as such, this book will additionally cover the robotic applications to many of the described urologic conditions. Laparoscopic urologic surgery is slowly becoming the surgery of choice in most urologic diseases, but as its application to reconstructive operations is a relatively new field, structured training is severely lacking in this area. This atlas therefore provides sequential pictures for most of the reconstructive urology procedures, with particular focus on pyeloplasty and ureteric reimplantation. Illustrations for each chapter on the whole come from a single case, with diagrammatic representation often also included to deepen clarity. In total the book contains 40 chapters, each offering a step-by-step illustrative approach, with specific reference to procedures directed at the following areas: - Kidney- Uretero Pelvic Junction- Ureter - Bladder- Prostate - Seminal vesical and undescended Testis. As such, this is an ideal reference work for all practicing urologists, surgical trainees and fully qualified surgeons, and also additionally, nurses and operation theatre technicians. With experience in the specialised training methodology required to produce successful results, within both developed and developing countries, the editors have further constructed the book in such a way that urologists will be able to perform the laparoscopic procedures described using simplified devices.